2020
DOI: 10.3390/jcm9010255
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Level and non-Protein Respiratory Quotient in Patients with Chronic Liver Diseases

Abstract: We sought to clarify the correlation between non-protein respiratory quotient (npRQ) in indirect calorimetry and serum zinc (Zn) level in chronic liver diseases (CLDs, n = 586, 309 liver cirrhosis (LC) patients, median age = 63 years). Clinical parameters potentially linked to npRQ <0.85 (best cutoff point for the prognosis in LC patients) were also examined in receiver operating characteristic curve (ROC) analyses. The median npRQ was 0.86. The median serum Zn level was 64 μg/dL. The median npRQ in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Moreover, multivariate analysis revealed that SGA is more closely associated with the npRQ than previously reported markers such as the Child-Pugh and ALBI scores, the branched-chain amino acid-to-tyrosine ratio, and serum zinc levels. [17][18][19][20] In terms of discriminative ability, SGA categories B and C displayed similar sensitivity and higher speci city compared to a FFA >660 μEq/L, leading to higher PPV and NPV for SGA than those observed for FFA. The strong link between SGA and energy malnutrition can be attributed to the components evaluated by the SGA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, multivariate analysis revealed that SGA is more closely associated with the npRQ than previously reported markers such as the Child-Pugh and ALBI scores, the branched-chain amino acid-to-tyrosine ratio, and serum zinc levels. [17][18][19][20] In terms of discriminative ability, SGA categories B and C displayed similar sensitivity and higher speci city compared to a FFA >660 μEq/L, leading to higher PPV and NPV for SGA than those observed for FFA. The strong link between SGA and energy malnutrition can be attributed to the components evaluated by the SGA.…”
Section: Discussionmentioning
confidence: 99%